الإسهام النسبي لكل من بيئة التعلم الإبداعية وسمات شخصية المعلم في التنبؤ بالتعلم الإبداعي لدى طلبة مدرسة STEM بالزقازيق - خريبه، إيناس محمد صفوت مصطفى (جامعة سوهاج - كلية التربية, 2021)
هدف البحث الحالي إلى تحديد مستوى التعلم الإبداعي وأبعاده، والكشف عن العلاقات الارتباطية بين التعلم الإبداعي وأبعاده وكل من بيئة التعلم الإبداعية وأبعادها وسمات شخصية المعلم، وتحديد الإسهام النسبي لكل من بيئة التعلم الإبداعية وسمات شخصية المعلم في التنبؤ بالتعلم الإبداعي لدى طلبة مدرسة STEM بالزقازيق. تكونت عينة البحث من (٢١٥) طالبًا وطالبة من طلبة الصفين الأول والثاني الثانوي بمدرسة STEM بالزقازيق. وتم تطبيق مقاييس التعلم الإبداعي وبيئة التعلم الإبداعية وسمات شخصية المعلم (إعداد الباحثة)، وبعد إجراء العمليات الإحصائية المناسبة لفرضيات البحث باستخدام معامل ارتباط بيرسون وتحليل الانحدار تم التوصل إلى: وجود مستوى مرتفع من التعلم الإبداعي وأبعاده، وجود علاقة ارتباطية موجبة دالة إحصائيا عند مستوى (0.01) بين درجات بيئة التعلم الإبداعية وأبعادها والتعلم الإبداعي ككل، وبين درجات بعد ممارسات المعلم وبعد التسهيلات والتجهيزات كأبعاد لبيئة التعلم الإبداعية وكل من البعد المعرفي والبعد الوجداني والبعد الاجتماعي والبعد المهارى للتعلم الإبداعي، ووجود علاقة ارتباطية موجبة دالة إحصائيا عند مستوى (0.05) بين درجات بعد التفاعل الإيجابي كأحد أبعاد بيئة التعلم الإبداعية والبعد المعرفي للتعلم الإبداعي، ووجود علاقة ارتباطية سالبة دالة إحصائيا عند مستوى (0.01) بين درجة سمات شخصية المعلم (العصابية) والدرجة الكلية للتعلم الإبداعي وأبعاده، ووجود علاقة ارتباطية موجبة دالة إحصائيًا عند مستوى (0.01) بين درجات سمات شخصية المعلم (الانبساطية، والتقبل، والضمير الحي، والانفتاح على الخبرات) والدرجة الكلية للتعلم الإبداعي وأبعاده، ووجود تأثير دال إحصائيا لجميع أبعاد بيئة التعلم الإبداعية وجميع سمات شخصية المعلم على الدرجة الكلية للتعلم الإبداعي لدى طلبة مدرسة STEM بالزقازيق.
The recent research aimed to identify the level of creative learning and its dimensions, explore relationships between creative learning and its dimensions (dependent variable) and creative learning environment and its dimensions and teacher’s personality traits (independent variables), and to identify relative contribution of creative learning environment and teacher’s personality traits in predicting creative learning among STEM school students in Zagazig. Research sample consisted of (215) male and female students from 1st and 2nd secondary stage in STEM school in Zagazig. Measures of creative learning, creative learning environment, and teacher’s personality traits (prepared by the researcher) were applied. After conducting suitable statistical operations using Pearson correlation coefficient and regression analysis, results were: there is a high level of creative learning and its dimensions, there is a statistically significant positive correlation at (0.01) level between creative learning environment and its dimensions scores and creative learning as a whole, and between teacher’s practices dimension and facilities and equipmments dimension scores as creative learning environment dimensions and cognitive dimension, emotional dimension, social dimension, and skill dimension of creative learning, there is a statistically significant positive correlation at (0.05) level between positive interaction dimension of creative learning environment and cognitive dimension of creative learning, there is a statistically significant negaitive correlation at (0.01) level between neouroticism and total score of creative learning and its dimensions, there is statistically significant positive correlation at (0.01) level between extraversion, agreeableness, conscientiousness, and openness to experience and total score of creative learning and its dimensions, and there is a stastically significant effect of all creative learning environment dimensions and all teacher’s personality traits on total score of creative learning among STEM school students in Zagazig.
Keywords: التعليم الثانوي -- التعلم الإبداعي -- بيئة التعلم الإبداعية -- سمات شخصية المعلم -- مدرسة STEM -- مدينة الزقازيق -- مصر